Origin of troctolites from Seljalandsheiði and Hrólfsvík, Iceland - Viktor Þór Georgsson 1987- (2019)
The chemical composition of 10 troctolite xenoliths was determined by electron microprobe analysis. The xenoliths come from two locations that are situated on distinct volcanic zones in Iceland, five from the “ankaramite” quarry of Seljalandsheiði, Eyjafjöll, and five from the bay of Hrólfsvík on the Reykjanes peninsula. To compare troctolites from these localities, all components of the samples roctolites were analyzed, including olivine, plagioclase, clinopyroxene, oxides and glass. The troctolites cover a large compositional range. The frorsterite content of olivine from Seljalandsheiði is 56.8-80.8, while that of the Hrólfsvík olivine varies between 77.2-88.1. Plagioclase from Seljalandsheiði and Hrólfsvík has anorthite content range of 69.3-86.5 and 79.9-92.3, respectively. Seljalandsheiði and Hrólfsvík clinopyroxene has Mg# between 72-84 and 83-88, respectively. Formation temperatures and pressures were calculated with multiple thermobarometers (olivine-liquid, plagioclase-liquid and clinopyroxene-liquid). The temperature range for Seljalandsheiði was 1134-1238°C. A discrepancy was noticed between olivine-liquid and plagioclase-liquid thermometers probably due to the high H2O content of melt in the Eyjafjöll region. The Hrólfsvík temperature range was 1082-1248°C. Pressure was only calculated with the clinopyroxene-liquid barometer and found to be 4.4-5.8 kbar ±1.4 kbar at Seljalandsheiði and 0.4-6.3 kbar ±1.4 kbar at Hrólfsvík. Interestingly troctolites seem to be crystalizing all over the crust at Hrólfsvík while they are confined to the upper part of the lower crust at Seljalandsheiði. Olivine-spinel pairs were used to calculate oxygen fugacity for the samples. The results show a large range in the calculated oxygen fugacity for Seljalandsheiði, between +0.34 and +1.15 logarithmic units relative to the quartz-fayalite-magnetite buffer (ΔlogfO2). Calculated ΔlogƒO2 for Hrólfsvík is lower and has a narrower range, between -0.97 and -0.19. Efnagreiningar voru gerðar á tíu troktólít framandsteinum frá ...